2012
DOI: 10.1029/2012eo260001
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the nation's carbon storage potential

Abstract: Carbon sequestration is a method of securing carbon dioxide (CO2) to prevent its release into the atmosphere, where it contributes to global warming as a greenhouse gas. Geologic storage of CO2 in porous and permeable rocks involves injecting high‐pressure CO2 into a subsurface rock unit that has available pore space. Biologic carbon sequestration refers to both natural and anthropogenic processes by which CO2 is removed from the atmosphere and stored as carbon in vegetation, soils, and sediments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The previous examples of area‐thickness‐porosity requirements show the paramount importance of porosity and formation thickness in determining the area over which fractured, geologic formation must extend to offer the magnitude of pore volume needed for large‐scale CO 2 injection. Assessment studies are underway in several countries to determine the available volume for the safe injection of CO 2 (International Energy Agency ; U.S. Department of Energy ; Warwick and Zhu ). A 2012 report by the International Energy Agency has shown that the current activity in CCS is small, mostly of an experimental nature.…”
Section: Injection Geologic Storage and Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous examples of area‐thickness‐porosity requirements show the paramount importance of porosity and formation thickness in determining the area over which fractured, geologic formation must extend to offer the magnitude of pore volume needed for large‐scale CO 2 injection. Assessment studies are underway in several countries to determine the available volume for the safe injection of CO 2 (International Energy Agency ; U.S. Department of Energy ; Warwick and Zhu ). A 2012 report by the International Energy Agency has shown that the current activity in CCS is small, mostly of an experimental nature.…”
Section: Injection Geologic Storage and Monitoringmentioning
confidence: 99%
“…The calculated areas vary from thousands to millions of squared kilometers depending on the effective porosity, formation thickness, and injected volume. Yet, accurate worldwide assessments may reveal that safe storage capacity for large‐scale capture and geologic storage that would be meaningful in reducing atmospheric CO 2 emissions may exist (U.S. Department of Energy ; Warwick and Zhu ). Why then the puny advance of capture and geologic storage?…”
Section: Capture Conveyance and Injection Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…During 2013, the USGS plans to prepare reports that contain the data used in the assessment, the assessment results, and an executive summary for on-line publication at http://energy.usgs.gov. Geologic CO 2 storage capacity may be much larger than biologic capacities, and likely ranges from hundreds to thousands of PgC in the geologic formations of the United States (Warwick and Zhu, 2012). The biologic and geologic national-scale assessments, when complete, will provide the most comprehensive accounting of the carbon storage potential in the United States.…”
Section: Definition Of Geochemical System:mentioning
confidence: 99%
“…Coal, a natural cost-effective geological medium, has been reported to be promising for geological GHG sequestration owing to its worldwide distribution and abundance. Coal also has great affinity for adsorption, but the CO 2 has the potential for low-level leakage after placement. In addition, the low rate of hydrates formation, a main obstacle to the application of the hydrates-forming technology, has been overcome by introducing an accelerating agent including sodium dodecyl sulfate (SDS) and cyclopentane. , Although carbon dioxide capture within deep unminable coal-beds has been proposed, little experimental study on storing CO 2 gas as hydrates in coal has been reported. Coal, as a medium material seems to be useful for entrapping carbon dioxide gas in the form of CO 2 hydrates through the hydrates-forming method with the aid of accelerating techniques.…”
Section: Introductionmentioning
confidence: 99%